A novel homozygous mutation (1619delC) in GPIIb gene associated with Glanzmann thrombasthenia, the decay of GPIIb-mRNA and the synthesis of a truncated GPIIb unable to form complex with GPIIIa - Losonczy, Gergely; Rosenberg, Nurit; Kiss, Csongor; Kappelmayer, János; Vereb, György; Kerényi, Adrienne; Balogh, István; Muszbek, László (Thrombosis and Haemostasis, 2005)
The absence of agonist-induced platelet aggregation and the lack of fibrinogen receptor (GPIIb/IIIa) on the platelet surface demonstrated that the severe hemorrhagic complications of a child of Romany descent were caused by Glanzmann thrombasthenia. DNA sequencing revealed a novel homozygous deletion of a cytosine (1619delC) in the GPIIb gene causing a frameshift and predicting a novel stop codon at position 533 following 24 altered amino acids. Both parents possessed the same deletion in heterozygous form. The amount of GPIIb mRNA in the patient’s platelets was 0.06% of the amount measured in control platelets. Neither GPIIb nor its truncated form could be detected in the platelets of the patient by Western blotting, while a small amount of GPIIIa was demonstrated. Quantitative flow cytometric analysis showed an elevated number of vitronectin receptors, a component of which is GPIIIa, on the patient’s platelets. The surface expression of vitronectin receptor on thrombasthenic, but not on normal platelets was further increased by activation with thrombin receptor agonist peptide. BHK cells transfected with wild type GPIIIa and mutated GPIIb failed to express any mature GPIIb or pro-GPIIb. Immunoprecipitation with a polyclonal antibody recognizing both GPIIb and GPIIIa recovered a 60 kDa truncated form of GPIIb. This band was absent when immunoprecipitation was carried out with an antibody recognizing GPIIIa, suggesting that the truncated protein, lacking calf-1, calf-2 domains and major part of the thigh domain, is unable to form complex with GPIIIa.
Keywords: Fibrinogen receptor; Glanzmann thrombasthenia; glycoprotein IIb mutation; truncated glycoprotein IIb; vitronectin receptor